Quantitative analysis of the solute redistribution and precipitate of Al–Mg–Si series alloys resistance spot welds after post–weld heat treatment - Yu Zhang (Elsevier, 2021)
In this study, an analytical model was established for calculating solute distribution pattern and precipitates of the Al–Mg–Si series alloys resistance spot welds. By coupling the model with a thermodynamic database, a volume element Ω was considered, then used to calculate the effective Mg and Si concentration in α-Al solid solution under different post–weld heat treatment. Resistance spot welding test of Aluminum alloys 6061 and 6082 was carried out, followed by sample characterization via transmission electron microscopy (TEM). Analysis of β-Mg2Si phase's distribution revealed that Mg and Si were segregated at the inter-granular region after welding. Notably, the β-Mg2Si phase was dissolved during post-welding solid solution treatment, thereby making Mg and Si to diffuse into the inner-granular region. This solute redistribution process was consistent with C-fS curves evolution calculated by the analytical model. The calculated effective Mg and Si concentration set up a platform for further calculation of precipitate evolution curves. Precipitate mole fraction was positively correlated with the weld's strength.